Breathless : a novel - Koontz, Dean R. (Dean Ray), 1945- (Bantam Books, 2009)
When Colorado carpenter Gary Adams spots two mysterious creatures in the woods near his house, he calls on his friend, veterinarian Cammy Rivers for advice. But like Gary, Cammy has never seen an animal resembling this beautiful species. But when the Department of Homeland Security puts a call out for Gary and Cammy because of these animals, the two risk everything to protect the innocent creatures.